Smaller Epiphyseal Tubercle and Larger Peripheral Cupping in Slipped Capital Femoral Epiphysis Compared with Healthy Hips: A 3-Dimensional Computed Tomography Study. (2nd January 2020) - Novais, Eduardo N.; Maranho, Daniel A.; Vairagade, Amishi; Kim, Young-Jo; Kiapour, Ata
Abstract : Background: The inner surface of the capital femoral epiphysis is important for growth plate stability. However, abnormalities of epiphyseal morphology associated with the pathogenesis of slipped capital femoral epiphysis (SCFE) remain poorly understood. This study compares the 3-dimensional anatomy of the epiphyseal tubercle and peripheral cupping in hips with SCFE and normal hips. Methods: We created 3-dimensional models of the capital femoral epiphysis with use of computed tomography (CT) imaging from 51 patients with SCFE and 80 subjects without hip symptoms who underwent CT because of abdominal pain. The height, width, and length of the epiphyseal tubercle and the peripheral cupping were measured and normalized by the epiphyseal diameter and presented as a percentage. We used analysis of variance for the comparison of the measurements between SCFE and control hips after adjusting for age and sex. Results: Compared with normal hips, hips with mild SCFE had smaller mean epiphyseal tubercle height (0.9% ± 0.9% compared with 4.4% ± 0.4%; p = 0.006) and length (32.3% ± 1.8% compared with 43.7% ± 0.8%; p < 0.001). The mean epiphyseal tubercle height was also smaller in hips with moderate (0.6% ± 0.9%; p = 0.004) and severe SCFE (0.3% ± 0.8%; p < 0.001) compared with normal hips. No differences were observed for measurements of epiphyseal tubercle height and length between SCFE subgroups. The mean peripheral cupping was larger in hips with mild (16.3% ± 1.0%; p < 0.001), moderate (16.4% ± 1.1%; p < 0.001), and severe SCFE (18.9% ± 0.9%; p < 0.001) overall and when assessed individually in all regions compared with normal hips (10.6% ± 0.5%). Conclusions: Hips with SCFE have a smaller epiphyseal tubercle and larger peripheral cupping compared with healthy hips. A smaller epiphyseal tubercle may be a predisposing morphologic factor or a consequence of the increased shearing stress across the physis secondary to the slip. Increased peripheral growth may be an adaptive response to instability as other stabilizers (i.e., epiphyseal tubercle and anterior periosteum) become compromised with slip progression. Future studies are necessary to determine the biomechanical basis of our morphologic findings.